Wiki en la Universitat Autònoma de Barcelona. Alcance y perspectivas - Sergi Robles (Universitat Politècnica de València, 2011)
RESUMEN Desde mayo del año 2004, un grupo de profesores de la Universitat Autònoma de Barcelona ha llevado a cabo distintas experiencias docentes en educación superior enfocadas a los nuevos planes piloto definidos en el marco del Espacio Europeo de Educación Superior (EEES) basadas en la utilización del wiki, con el fin de mejorar el proceso de enseñanza-aprendizaje de los estudiantes. Se han desarrollado distintos materiales docentes para el aprendizaje autónomo y semi-presencial, diseñados para potenciar el trabajo colaborativo y a distancia. El análisis de los resultados obtenidos con la aplicación del wiki a la docencia ha permitido identificar las ventajas y las carencias del sistema de trabajo inicial y ampliar sus posibilidades con herramientas que aseguran una mejor adaptación de esta plataforma al EEES. La labor desarrollada por el grupo y el interés despertado en la comunidad universitaria son el punto de partida de la integración del wiki en el Campus Virtual (la plataforma institucional de soporte virtual del aprendizaje de la Universitat Autònoma de Barcelona) que se está llevando a cabo actualmente. ABSTRACT Since May 2004, a group of instructors of the Universitat Autònoma de Barcelona has been involved  in different experiences of  innovation on higher education, within the European Space of Higher Education (ESHE), regarding the use of a wiki system to improve the teaching and learning process of students. The group has focused on the development of educational activities, mainly addressed for self-directed learning and blended learning, created to strengthen collaborative work and e-learning. The experiences of the group with the use of wiki have allowed  to determine the strengths and weaknesses of using the wiki platform for higher education. Using this, the group has included some new tools in the wiki system in order to improve the teaching possibilities, especially those related to the ESHE. The work developed by the group and the interest sparked by this system within the community of the university are the starting point towards the integration of the wiki in the Campus Virtual (the institutional virtual learning support platform of the Universitat Autònoma de Barcelona), which is currently being undertaken.